EXAMINING MADRASAH TSANAWIYAH STUDENTS' PROBLEM-SOLVING ABILITIES IN SOLVING MAWARIS-INTEGRATED FRACTION WORD PROBLEMS - Syaifudin Syaifudin; Rohman Rohman; Luvi Antari; Ria Erviana (Program Studi PGSD Universitas Flores, 2026)
Mathematical problem-solving ability is an essential competency that enables students to apply mathematical concepts in real-life situations. However, many students still encounter difficulties when solving fraction word problems, particularly those involving contextual and religiously relevant situations. This study aimed to investigate the problem-solving abilities of Madrasah Tsanawiyah (MTs) students in solving fraction word problems integrated with Mawaris (Islamic inheritance) contexts. A descriptive qualitative approach was employed involving 22 ninth-grade students of MTs Muqimus Sunnah. Data were collected through problem-solving tests, interviews, and documentation and were analyzed based on four indicators of problem solving: understanding the problem, devising a plan, carrying out the plan, and interpreting the results. The findings showed that 27.27% of students were categorized as having high problem-solving ability, 45.45% moderate ability, and 27.27% low ability. Students performed best in understanding the problem and carrying out the solution plan (72.73%), while interpreting the results was the weakest indicator (36.36%). Difficulties mainly arose in translating contextual information into mathematical models, performing fraction operations accurately, and relating solutions to the Mawaris context. The study concludes that integrating Mawaris into fraction learning provides meaningful contextualization and can support the development of students’ mathematical problem-solving abilities while strengthening Islamic values.